Tracking systems in navigated lower abdominopelvic surgery, a review - Aguilera Saiz, Laura; Groen, Harald C.; Heerink, Wouter J.; Ruers, Theo J.M. (Clinical Surgical Oncology, 2025)
The lower abdominopelvic region is characterized by complex anatomy harbouring many vital structures in a constrained area. Advanced guidance can enhance the precision and efficiency of lower abdominopelvic surgical procedures. This can be achieved with image-guided surgical navigation systems, which use preoperative data to display real-time updates of intraoperative data. The current literature review explores the current state and prospective approaches for developing clinical navigation systems tailored for the lower abdominopelvic region. We aim to identify current knowledge gaps and technological challenges in navigation and explore potential solutions proposed in the literature. A comprehensive literature review of the current state of the art of navigation systems was performed. Relevant clinical and technical information from the publications was extracted and added value of navigation systems was analysed. According to the reviewed literature, existing commercial navigation systems focus mainly on rigid structure navigation. Despite being certified for spine, hip, knee and neurosurgery, commercial systems were used in 16 out of 29 studies for non-rigid pelvic surgery, which was outside their intended use. Comparative studies showed that navigation was of added value for surgical efficiency and clinical outcomes. Navigation in lower abdominopelvic surgeries contributed to more precise resection margins and reduction of local recurrences, resulting in more precise and safe surgeries. Various promising navigation systems show high performance in lower abdominopelvic surgery. However, their implementation is mainly examined in feasibility studies. Consequently, the use of navigation systems in clinical standard routine still remains limited. [Display omitted] •There is a need for image-guided navigation systems tailored for lower abdominopelvic surgery.•Commercially available systems are not customized for lower abdominopelvic surgery.•Commercially available systems are reliable for lower abdominopelvic surgery.•Further efforts should concentrate on advancing current research systems.•Reliable deformable registration can facilitate clinical translation.